Checkmate - Dunnett, Dorothy (Dunnett, Dorothy. Lymond chronicles, 2019)
It is now 1557 and Lymond has returned to France to marshal forces in the Scottish struggle against England. But even as he attains brilliant success on the battlefield, his haunted past becomes a subject of intense interest to both sides. For whoever knows the secret of Lymond's parentage possesses the power to control him--or destroy him. With his country, his family, his great love, and his very life at stake, it's time for Lymond to make his final moves.